Deep learning neural network for time series water level forecasting - Zaini N.; Malek M.A.; Norhisham S.; Mardi N.H. (Springer Science and Business Media Deutschland GmbH, 2023)
Deep neural networks; Flood control; Forecasting; Learning systems; Long short-term memory; Mean square error; Offshore oil well production; Time series; Water levels; Coefficient of determination; Daily time series; Forecasting models; Learning neural networks; Learning techniques; Root mean square errors; Training and testing; Water level forecasting; Deep learning